1990
DOI: 10.1111/j.1365-246x.1990.tb01786.x
|View full text |Cite
|
Sign up to set email alerts
|

Time- and frequency-dependent polarization analysis: anomalous surface wave observations in Iberia

Abstract: S U M M A R YA time-and frequency-dependent polarization method is applied to synthetic and observational data in order to investigate effects of lateral heterogeneity on surface wave polarization. It is shown that interference of surface wave signals can produce artifacts in the polarization as determined for the dominant signal present in the data.The time-and frequency-dependent polarization technique is applied to surface waves recorded in Iberia to investigate the character of the recorded wavetrains. Ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…They confirmed the presence of significant refraction and multipathing. On data recorded in Iberia, Paulssen et al (1990) performed a time‐ and frequency‐dependent polarization analysis and suggested that the anomalous surface wave observations could be due to the interference of surface wave signals. More recently, Levshin et al (1994) studied polarization anomalies observed in the former Soviet Union for surface waves crossing northern and central Eurasia, and showed how a regional structure showing lateral heterogeneities in the crust and upper mantle can cause large deviations from great‐circle propagation.…”
Section: Introductionmentioning
confidence: 99%
“…They confirmed the presence of significant refraction and multipathing. On data recorded in Iberia, Paulssen et al (1990) performed a time‐ and frequency‐dependent polarization analysis and suggested that the anomalous surface wave observations could be due to the interference of surface wave signals. More recently, Levshin et al (1994) studied polarization anomalies observed in the former Soviet Union for surface waves crossing northern and central Eurasia, and showed how a regional structure showing lateral heterogeneities in the crust and upper mantle can cause large deviations from great‐circle propagation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, since surface waves sample primarily the highly heterogeneous crust and uppermost mantle, they are subject to strong path effects, manifested in the form of lateral refraction and multipathing. Since regional seismic structure can vary sharply over the scale of one wavelength and teleseismic wavefields often exhibit serious distortions in phase and amplitude [e.g., Bungum and Capon, 1974;Paulssen et al, 1990], ray theory combined with the assumption of "plane" incoming wavefields are only an approximate means of performing regional surface wave tomography [Friederich et al, 1994] (hereinafter referred to as FWS94). Ray theory is justified in most global tomographic studies [e.g., Trampert and Woodhouse, 1995; Ekstr•m et al, 1997], where the minimum modeled wavelength of Earth structure is much larger than the wavelengths of the propagating waves that sample it.…”
Section: Paper Number 1999jb900118mentioning
confidence: 99%
“…In the interactive analysis of Plešinger et al (1986), one seeks the local coordinate system for which certain component products are zero. Paulssen et al (1990) expanded the basic timefrequency analysis for the three-component seismograms and presented the time and frequency-dependent polarization of anomalous surface waves observed at stations on the Iberian Peninsula. Paulssen et al (1990) expanded the basic timefrequency analysis for the three-component seismograms and presented the time and frequency-dependent polarization of anomalous surface waves observed at stations on the Iberian Peninsula.…”
Section: Other Surface Wave Observablesmentioning
confidence: 99%